PROPOSED CORPORATE STRATEGY TO DRIVE SUSTAINABLE IN FUTURE BY USING HEXAGONAL RESTRUCTURING (CASE STUDY IN PT PERKEBUNAN NUSANTARA VIII) (The Indonesian Journal of Business Administration, 2020)
PT Perkebunan Nusantara (PTPN) VIII is a state-owned enterprise (BUMN) that has been established since March 11, 1996, PTPN VIII is a state-owned company engaged in agribusiness and agroindustry with business activities including cultivation, land preparation, nursery, planting, maintenance, management and sales of plantation commodities and optimizing the utilization of company resources amounting to 113,958 ha, which consists of two provinces (West Java and Banten). The agricultural sector itself is included in the 4 biggest industries in Indonesia, this is because Indonesia itself gets bonus topography, soil structure, and weather that strongly supports the agricultural business. At present PTPN VIII out of 113,958 ha of land that has been given by the government, there is still 47,145.11 ha that has not been productive in producing agricultural products, and it is alleged that PTPN VIII made efforts to utilize land resources by developing business towards the property business (hotels, apartments, houses) with the goal is that the land owned has added value and continues to provide benefits. Based on external analysis and internal analysis as well as SWOT analysis for PTPN VIII, that the strength of PTPN VIII is the condition of Indonesia that supports plantation business activities, but still has shortcomings in the application of technology and business processes in plantation business operations and doing business outside the plantation business in collaboration with parties three, and faced with the challenges of changing natural conditions. This research shows that PTPN VIII is in the position of a company that needs restructuring, based on the TOWS Matrix, produces several strategies which include improving corporate governance that is more focused on the plantation business, making improvements in the field of operations so that it can produce better commodities, make innovations in technology and products produced by PTPN VIII. Based on Hexagonal Restructuring there are still significant differences between PTPN VIII and competing companies, and PTPN VIII needs to sell assets owned but not related to agricultural businesses such as hospital businesses and property businesses and unproductive assets so that the cash owned can be used for the development and innovation of PTPN VIII in the plantation sector. Keywords: Corporate Strategy, SWOT Analysis, TOWS Matrix, Hexagonal Restructuring